Pull Factors and Capital Inflows: Empirical Insights from Transformative Dynamics in Southeast Europe - Ganić, Mehmed; Gavranović, Nedim (Naše gospodarstvo/Our economy, 2024)
This study seeks to examine pull factors of capital inflows, offering an empirical analysis based on a panel study of eleven Southeast European countries (Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Montenegro, North Macedonia, Kosovo, Romania, Serbia, and Türkiye) over the period of 2004 – 2021. Methodologically, the study utilizes a fixed effects (FE) regression model with robust Driscoll-Kraay standard errors to address issues of heteroskedasticity, autocorrelation, and potential cross-country correlation. The study finds that several pull factors can be relevant in driving capital inflows as follows: market size, inflation, financial and trade openness. The empirical analysis confirms that the forces of trade liberalization, financial liberalization, market size, real interest rates and inflation stability are the elements that encourage capital inflows. On the other hand, the estimated effects of current account balance and real economic growth are not very convincing. Finally, we stress that more study is required to fully understand the pull variables’ ultimate macroeconomic implications at the national level. The overall influence of these positive (or negative) inflows may be moderated by several characteristics, even if certain countries may be extremely susceptible to these factors.